PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP LOYALITAS KERJA KARYAWAN KANTOR PTPN III KEBUN MEMBANG MUDA: (Studi kasus pada Karyawan bagian Lapangan) - Nainggolan, Denada Putri BR; Sihombing, Marlon (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to analyze the effect of leadership style and organizational culture on work loyalty of employees in the field office of PTPN III Kebun Membang Muda. This research is quantitative research with associative methods. The population in this study consisted of 544 employees of PTPN III Kebun Membang Muda field, and the sampling method was purposive sampling with the slovin formula, resulting in a sample of 85 respondents. Primary data was obtained through direct survey distribution, and secondary data was obtained through books, journals and theses related to this research. Validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing were used in this study. According to the findings of this study, leadership style has a considerable impact on work loyalty. Workplace loyalty is positively influenced by organizational culture. Work loyalty is influenced by leadership style and organizational culture. Based on the coefficient of determination in this study, leadership style and organizational culture are able to explain 66.5% of the work loyalty variable. The rest is influenced by additional variables that are not discussed in this study.